2008
DOI: 10.1254/jphs.fp0071119
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Vasorelaxant Effect Induced by Proanthocyanidin-Rich Fraction From Croton celtidifolius in Rat Small Resistance Arteries

Abstract: Abstract. Proanthocyanidins are condensed tannins present in fruits, vegetables, and flowers, consumed in the human diet. These compounds are believed to decrease coronary heart disease. The present study was designed to investigate the relaxing effects of a proanthocyanidin-rich fraction (PRF) obtained from Croton celtidifolius BAILL (Euphorbiaceae) barks in rat mesenteric arterial bed (MAB) and isolated mesenteric artery (MA). In the MAB pre-contracted with phenylephrine (Phe), PRF (0.1 -100 µg) induced a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…21) 4-Aminopyridine and BaCl 2 significantly shifted the vasorelaxation curve to the right, and paxillin, apamin, and glybenclamide had a tendency to inhibit this effect. As DalBo et al 8) reported, BK Ca 2þ þ SK Ca 2þ inhibitors abolished the relaxation of procyanidins, although less abolition was observed for each inhibitor alone. This implies that blocking both small and large-conductance Ca 2þ -activated K þ channels can abolish AP relaxation (the combination experiment not done).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…21) 4-Aminopyridine and BaCl 2 significantly shifted the vasorelaxation curve to the right, and paxillin, apamin, and glybenclamide had a tendency to inhibit this effect. As DalBo et al 8) reported, BK Ca 2þ þ SK Ca 2þ inhibitors abolished the relaxation of procyanidins, although less abolition was observed for each inhibitor alone. This implies that blocking both small and large-conductance Ca 2þ -activated K þ channels can abolish AP relaxation (the combination experiment not done).…”
Section: Discussionmentioning
confidence: 76%
“…Dalbo et al 8) also reported that endothelium-dependent vasorelaxation of procyanidins from Croton celtidifolius was involved in the activation of Ca 2þ -dependent K þ channels. In contrast, Kwan et al 9) found that vasorelaxation due to procyanidin-rich extract was caused by the opening of multiple K þ channels.…”
Section: )mentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent study, we observed that proanthocyanidinrich fraction (PRF) mediates an endothelium-dependent vasorelaxant effect involving the NO-cGMP pathway and hyperpolarization induced by K Ca2+ channels activation in rat small resistance arteries (21). The aim of the current investigation is to determine the mechanisms of the PRF-induced vasodilator effect, using rat thoracic aorta.…”
Section: Increases In Intracellular Calcium Concentration ([Camentioning
confidence: 97%
“…Phytochemical studies of C. celtidifolius bark indicate the presence of cyclitols such as 1L-1-O-methyl-myo inositol, neo-inositol and sitosterol (Mukherjee & Axt, 1984), catechins and gallocatechins, proanthocyanidins (DalBó et al, 2008;Nardi et al, 2003), alkaloids and saponins (Amaral & Barnes, 1997). In Croton species containing red latex, only proanthocyanidin polymers of varying molecular weight have been characterized, comprising almost 90% of the red latex dry weight (Salatino et al, 2007).…”
Section: Introductionmentioning
confidence: 99%